A selective impairment of perception of sound motion direction in peripheral space: A case study. (8th January 2016) - Thaler, Lore; Paciocco, Joseph; Daley, Mark; Lesniak, Gabriella D.; Purcell, David W.; Fraser, J. Alexander; Dutton, Gordon N.; Rossit, Stephanie; Goodale, Melvyn A.; Culham, Jody C.
Abstract: It is still an open question if the auditory system, similar to the visual system, processes auditory motion independently from other aspects of spatial hearing, such as static location. Here, we report psychophysical data from a patient (female, 42 and 44 years old at the time of two testing sessions), who suffered a bilateral occipital infarction over 12 years earlier, and who has extensive damage in the occipital lobe bilaterally, extending into inferior posterior temporal cortex bilaterally and into right parietal cortex. We measured the patient's spatial hearing ability to discriminate static location, detect motion and perceive motion direction in both central (straight ahead), and right and left peripheral auditory space (50° to the left and right of straight ahead). Compared to control subjects, the patient was impaired in her perception of direction of auditory motion in peripheral auditory space, and the deficit was more pronounced on the right side. However, there was no impairment in her perception of the direction of auditory motion in central space. Furthermore, detection of motion and discrimination of static location were normal in both central and peripheral space. The patient also performed normally in a wide battery of non-spatial audiological tests. Our data are consistent with previous neuropsychological and neuroimaging results that link posterior temporal cortex and parietal cortex with the processing of auditory motion. Most importantly, however, our data break new ground by suggesting a division of auditory motion processing in terms of speed and direction and in terms of central and peripheral space. Highlights: Patient MC has lesions including posterior temporal and parietal cortex. MC has deficit in perception of sound motion direction in peripheral space. Division of auditory motion processing into speed vs. direction. Division of auditory motion processing into peripheral vs. central.